Maternal determinants of optimal breastfeeding and complementary feeding and their association with child undernutrition in Malawi (2015-2016) - Christine N. Walters; Hasina Rakotomanana; Joel J. Komakech; Barbara J. Stoecker (BMC, 2019)
Abstract Background Optimal breastfeeding and complementary feeding practices are critical to prevent child undernutrition. Despite the occurrence of child undernutrition and widespread suboptimal feeding practices in Malawi, the association of breastfeeding and complementary feeding practices and undernutrition among Malawian children remains unclear. The purpose of the study was to determine the current breastfeeding and complementary feeding practices, to identify maternal determinants of each practice, and to analyze the associations between breastfeeding and complementary feeding practices with stunting, underweight, and wasting. Methods The most recent Malawi Demographic Health Survey (2015-2016) was used and data for 2294 children aged 0-23 months were included. A conceptual framework of five maternal domains: sociodemographic, health status, health behaviors, women's empowerment, and media exposure was used. Each domain contained exposure variables and the WHO Infant and Young Child Feeding indicators were used as outcome variables. All analyses were adjusted for clustering, and variables that reached a p-value of < 0.05 were considered significant in the final model. Results Among children, 30.8% were stunted, 9.9% were underweight, and 3.7% were wasted. Many (78%) were breastfed within the first hour of birth, 89% were breastfed until their first birthday, yet 40% were not exclusively breastfed to 6 months. Only 32% met minimum dietary diversity, 23% met minimum meal frequency, 12% met minimum acceptable diet and 12% consumed iron-rich foods. Children whose mothers lived in urban areas were less likely to be breastfed within 1 hour of birth but more likely to meet minimum dietary diversity. Children whose mothers listened to radio were more likely to meet minimum meal frequency. Children (13-23 months) who met minimum meal frequency and minimum acceptable diet were less likely to be underweight. Conclusions Optimal breastfeeding and complementary feeding practices in Malawi remain suboptimal and child undernutrition remains problematic. Maternal characteristics from the five domains were significantly associated with optimal breastfeeding and complementary feeding indicators. Knowledge of these maternal determinants can assist in improving nutrition policies and interventions that aim to impact breastfeeding and complementary feeding practices and child growth in Malawi.